Use of ovitraps for the seasonal and spatial monitoring of Aedes spp. in an area endemic for arboviruses in Northeast Brazil - João Victor Oliveira Noleto; Hevilem Letícia Moura do Nascimento Moraes; Tamires de Moura Lima; João Gustavo Mendes Rodrigues; Diogo Tavares Cardoso; Kalyl Chaves Lima; Richardson Soares de Souza Melo; Guilherme Silva Miranda (Journal of Infection in Developing Countries)
Introduction: Due to recent outbreaks of Dengue and Chikungunya and an absence of effective monitoring of the mosquito Aedes spp. in the municipality of São Raimundo das Mangabeiras, State of Maranhão, we aimed to demonstrate the potential of ovitraps used together with mathematical models and geotechnology to improve control of this mosquito.